A genetic association study of activated partial thromboplastin time in European Americans and African Americans: the ARIC Study. (30th December 2014) - Weng, Lu-Chen; Cushman, Mary; Pankow, James S.; Basu, Saonli; Boerwinkle, Eric; Folsom, Aaron R.; Tang, Weihong
Abstract: Reduced activated partial thromboplastin time (aPTT) is a risk marker for incident and recurrent venous thromboembolism (VTE). Genetic factors influencing aPTT are not well understood, especially in populations of non-European ancestry. The present study aimed to identify aPTT-related gene variants in both European Americans (EAs) and African Americans (AAs). We conducted a genetic association study for aPTT in 9719 EAs and 2799 AAs from the Atherosclerosis Risk in Communities (ARIC) study. Using the Candidate Gene Association Resource (CARe) consortium candidate gene array, the analyses were based on ∼50 000 SNPs in ∼2000 candidate genes. In EAs, the analyses identified a new independent association for aPTT in F5 (rs2239852, P -value = 1.9 × 10 −8 ), which clusters with a coding variant rs6030 ( P -value = 7.8 × 10 −7 ). The remaining significant signals were located on F5, HRG, KNG1, F11, F12 and ABO and have been previously reported in EA populations. In AAs, significant signals were identified in KNG1, HRG, F12, ABO and VWF, with the leading variants in KNG1, HRG and F12 being the same as in the EAs; the significant variant in VWF (rs2229446, P -value = 1.2 × 10 −6 ) was specific to the AA sample (minor allele frequency = 19% in AAs and 0.2% in EAs) and has not been previously reported. This is the first study to report aPTT-related genetic variants in AAs. Our findings in AAs demonstrate transferability of previously reported associations with KNG1, HRG and F12 in EAs. We also identified new associations at F5 in EAs and VWF in AAs that have not been previously reported for aPTT.